The trend of individualization of the agricultural work in the families of the southern region of Brazil in the 90's - de Souza, M. (Agrociencia Uruguay, 2004)
Individualization consists in the idea that the process of agricultural production is starting to be run by only one person, the one who is responsible for the performance of the process, opposing the traditional familiar functioning structure in order to illustrate this occurring aspect in the south of Brazil, special tabulations of the micro data of the National Sample Home research (PNADs) were used for the period between 1992 and 1999. it was verified that the process of individualization affects differently the members of the family. Results show reliable trends of decrease in the average number of agricultural assets of the referred families, spouses and children. Moreover, a stronger reduction was noticed on the spouses and children´s assets. except two daughters, all the other positions in the families present simultaneous engagement with nonagricultural activities. In conclusion, rural families of the southern region of Brazil, especially the ones who are engaged in agricultural activities, are in an increasing process of redefinition that is reflected in new structures of work organization leading to a necessity of redefining the current public policies.